Spread of COVID-19 and citizens’ behaviour: a comparison of importance-compliance analyses among Bangladeshis and Malaysians - Rahman, Mahbubar; Islam, Rafikul; Mahmud, Md. Shahed (Inderscience, 2021)
Majority of the countries in the world are grappling with the onslaught of COVID-19 by engaging in various measures to safeguard the lives of citizens of their country. On this backdrop, the present research aims at identifying the attributes that governments need to pay increased attention. The perception data was collected from citizens of two countries i.e., Bangladeshis (n=102) and Malaysians (n=97). The Importance Compliance Analysis (ICA) was applied on 29 attributes for the two countries’ citizens and a comparison was made on the findings. Apart from ICA, Paired as well as Independent Sample t-tests were performed on the data collected. According to the findings (which are applicable for both countries) the respective government should take measures so that their citizens strictly adhere the recommended attributes. The study findings may also help other countries as well in limiting the spread of COVID-19.